1992
DOI: 10.1095/biolreprod47.2.213
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Platelet-Activating Factor Suppresses Uterine Oxytocin-Induced 13, 14-Dihydro-15-Keto-Prostaglandin F2α Release and Phosphatidylinositol Hydrolysis in the Ewe1

Abstract: This study was conducted to determine whether platelet-activating factor (PAF) (1) attenuated oxytocin-induced secretion of the prostaglandin (PG) F2 alpha metabolite, PGFM, by the ovine uterus in situ and (2) inhibited the generation of the inositol phosphate secondary messengers by endometrial tissue in response to oxytocin challenge in vitro. Ovariectomized ewes received steroid replacement to mimic the luteal phase. Six ewes received intrauterine injections of 200 micrograms PAF/uterine horn/day on Days 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 0 publications
2
16
1
Order By: Relevance
“…The mobilization of polyphosphated inositols in ovine endometrium by PAF treatment is consistent with this receptor being functional in this tissue (3). The sex hormone dependency of the PAF receptor expression (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The mobilization of polyphosphated inositols in ovine endometrium by PAF treatment is consistent with this receptor being functional in this tissue (3). The sex hormone dependency of the PAF receptor expression (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…However, the rapid action of PAF on the endometrium suggests that its effects may be primarily nongenomic. PAF is known to activate phospholipase A 2 in several cell types (3,17,22), and such action in the uterus may free arachidonic acid for PG synthesis (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The failure to detect significant stimulation of PLC activity or PGF2a synthesis on day 14 after oestrus is difficult to explain, particularly when stimulation was detected on days 13 and 15 in the present study and has been observed on day 14 in a previous study (Silvia and Raw, 1993 (Battye et al, 1992 (Miller et al, 1977 …”
Section: Experiments 2bcontrasting
confidence: 59%